A study on how to increase the sales of bamboo based products manufactured by Syarikat Majutani (KEDA) Sdn. Bhd. / Harun Ishak ... [et al.] - Ishak, Harun; Ismail, Abdul Rahman; Othman, Razzak Kamel; Mustaffa, Auziz; Aziz, Zulkifli; Hashim, Siti Hajar (1987)
Kedah Regional Development Authority was formed on the 26th of March 1981 through an Act of Parliment No:249. It was formed with the main aim to raise the standard of living of the people staying in the rural areas specifically outside the MUDA area.